Luz de America: comunidad y biodiversidad Amazonica - Zapata, D.M.O.; Gonzáles, L.A.; Larrea, J.F.; González, B.; Silva, E.; Arellanos, A.; Meo, S.; Jong, W. de (Center for International Forestry Research, 2003)
Problems with governance of forests are closely linked to incompatible interests between different stakeholders. Having a clearer understanding of the relative importance of forest landscape functions among stakeholders can bring much clarity about why governance problems persist. The voice of the weakest actors is often insufficiently heard in decision-making processes that affect how stakeholders can use forests. CIFOR has developed potentially rapid and efficient assessment procedures that, as far as possible, explicitly identify and describe what landscape functions that are most important for forest dependent communities. This Multidisciplinary Landscape Assessment (MLA) set of methods was developed in East Kalimantan, Indonesia. The “Stakeholders and biodiversity in the forest of the future project” tested and further developed the MLA methods in Bolivia (humid forest) and Mozambique (woodlands).